2021
DOI: 10.1111/jgh.15479
|View full text |Cite
|
Sign up to set email alerts
|

Use of a convolutional neural network for classifying microvessels of superficial esophageal squamous cell carcinomas

Abstract: Background and Aim:The morphological diagnosis of microvessels on the surface of superficial esophageal squamous cell carcinomas using magnifying endoscopy with narrow-band imaging is widely used in clinical practice. Nevertheless, inconsistency, even among experts, remains a problem. We constructed a convolutional neural network-based computer-aided diagnosis system to classify the microvessels of superficial esophageal squamous cell carcinomas and evaluated its diagnostic performance. Methods: In this retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…From these we identified 67 separate articles that appeared to be relevant to the study question. In total, 42 studies 17‐58 reported on the performance of AI in the diagnosis of various ODs and were included in the qualitative synthesis (Supplementary Table S1). Among the included studies, 19 17‐35 reported complete data for extraction and were included in the meta‐analysis: 9 on BN, 17‐25 5 on OSCC, 26‐30 2 on abnormal IPCLs 31,32 and 3 on GERD 33‐35 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From these we identified 67 separate articles that appeared to be relevant to the study question. In total, 42 studies 17‐58 reported on the performance of AI in the diagnosis of various ODs and were included in the qualitative synthesis (Supplementary Table S1). Among the included studies, 19 17‐35 reported complete data for extraction and were included in the meta‐analysis: 9 on BN, 17‐25 5 on OSCC, 26‐30 2 on abnormal IPCLs 31,32 and 3 on GERD 33‐35 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…From these we identified 67 separate articles that appeared to be relevant to the study question. In total, 42 studies 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 reported on the performance of AI in the diagnosis of various ODs and were included in the qualitative synthesis (Supplementary Table S1 ). Among the included studies, 19 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dedicated models analyzing WLI and NBI images have shown high disease-specific diagnostic accuracy not only for BE and EAC [ 4 ] but also for esophageal squamous cell carcinoma (ESCC) [ 5 ]. Dedicated algorithms have also been implemented to analyze enhanced endoscopy imaging, allowing to evaluate disease-specific mucosal and vascular patterns [ 6 ], the presence of submucosal invasion [ 7 ], the depth of invasion [ 8 ], and microendoscopy use for both ESCC [ 9 ] and BE [ 10 ]. Moreover, a recent meta-analysis has shown an overall high accuracy in the detection of early EAC, with a significantly better performance compared to endoscopists in terms of the pooled sensitivity (0.94 vs. 0.82, p = 0.01).…”
Section: Upper Gastro-intestinal Tractmentioning
confidence: 99%
“…However, NBI is beneficial to enhance histological diagnostic grading accuracy [ 6 ]. Moreover, NBI can enhance the ability to differentiate squamous cell carcinoma microvessels [ 20 ]. A multi-center study shows that magnifying endoscopy narrow-band imaging (ME-NBI) reached senior endoscopic physicians’ predictive performance in early gastric cancer.…”
Section: Application Of DL In Gastrointestinal Endoscopymentioning
confidence: 99%